2020
DOI: 10.1016/j.arr.2020.101124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of influenza vaccination on the risk of cardiovascular and respiratory diseases and all-cause mortality

Abstract: Highlights Compared to unvaccinated people, influenza-vaccinated people had the risk reduction of 26% for cardiovascular diseases (63 studies), 18% for respiratory diseases (29 studies), and 43% for all-cause mortality (43 studies). Influenza vaccination was associated with reduced risk of stroke, myocardial infarction, acute coronary syndrome (ACS), heart failure, ischemic heart disease (IHD), major adverse cardiovascular events (MACEs), and cardiovascular mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 111 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Other investigations conducted in different Brazilian cities (studies with a smaller number of older participants) report not wanting to receive the vaccine [21,29,30], believing that it will provoke a reaction [21][22][23]31], a lack of counseling from health providers [22], forgetfulness [21,22], "never getting the flu" [29] and not thinking that the vaccine is necessary [22,31] as justifications offered by older people for nonadherence. Studies on influenza vaccination for older people, who are particularly vulnerable to negative outcomes from influenza infection, are becoming increasingly relevant due to the rapid growth of this age group in the Brazilian population [24] and the importance of the vaccine as a public health strategy for the prevention of complications resulting from such infection [12,14].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations conducted in different Brazilian cities (studies with a smaller number of older participants) report not wanting to receive the vaccine [21,29,30], believing that it will provoke a reaction [21][22][23]31], a lack of counseling from health providers [22], forgetfulness [21,22], "never getting the flu" [29] and not thinking that the vaccine is necessary [22,31] as justifications offered by older people for nonadherence. Studies on influenza vaccination for older people, who are particularly vulnerable to negative outcomes from influenza infection, are becoming increasingly relevant due to the rapid growth of this age group in the Brazilian population [24] and the importance of the vaccine as a public health strategy for the prevention of complications resulting from such infection [12,14].…”
Section: Plos Onementioning
confidence: 99%
“…Vaccinated individuals are at a lower risk of developing influenza and similar respiratory conditions [ 12 , 13 ]. Moreover, vaccination is associated with a reduction in the risk of hospitalization and death not only due to influenza and pneumonia, but also due to cardiovascular disease and is associated with a reduction in the risk of all-cause mortality [ 14 ]. Recent studies suggest a possible adjuvant effect of the flu vaccine on the reduction in the severity of Covid-19 (Sars-Cov-2) as well as the mortality rate related to this infection [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Restivo et al [39] reported that influenza vaccine effectiveness was 39% (95%CI: 32-46%) for hospital visits and 57% (95%CI: 30-74%) for hospitalization among children, and the rate was 25% (95%CI: 6-40%) for visits and 14% (95%CI: 7-21%) for hospitalization among older adults. Cheng et al [40] conducted a meta-analysis that included 29 studies and found that influenza vaccination was associated with a lower risk of overall adversary respiratory outcomes (including asthma, chronic obstructive pulmonary disease, unspecific respiratory diseases, respiratory failure, respiratory infections, pneumonia, and respiratory mortality) in the group aged over 65, from which significant associations were detected between influenza vaccination and pneumonia (aRR 0.79, 95% CI: 0.65−0.95) and respiratory mortality (aRR 0.79, 95 % CI: 0.67−0.92). These results showed that influenza vaccination was effective at protecting vulnerable populations from influenza and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, vigorous efforts should be made towards vaccine development for COVID-19. Influenza vaccine can reduce the risk of cardiovascular events by 26-35% and all-cause mortality by 43% in the general adult population [96,97]. For high-risk patients with a history of recent AMI, influenza vaccination was of significant benefit because it reduced the risk of cardiovascular events by 55% [96].…”
Section: Discussionmentioning
confidence: 99%